THE EFFECT OF MENTORING ON SECONDARY SCHOOLS SCIENCE STUDENTS’ ATTITUDE TOWARDS ENVIRONMENTAL PRACTICES IN URBAN LOCATION - Olu-Ajayi, Funmilayo Elizabeth (PEOPLE: International Journal of Social Sciences, 2019)
There is the need for a sustainable environment and to build a sustainable future, especially in densely populated and urban areas. This is imperative to the wellbeing of inhabitants and development of the society. The study investigated the effect of mentoring on secondary schools science students’ attitude towards environmental practices in urban location. The research design was quasi-experimental of non-randomized pre-test, post-test, control group system. The population for the study was made up of science students in public senior secondary schools in Nigeria. The sample size was 200, selected through simple random and purposive sampling techniques. A validated questionnaire titled ‘Environmental Attitude Rating Scale’ (EARS) which was adjudged to be reliable, having a coefficient value of 0.68 obtained using test-retest method was used to gather data for the study. Supplemental Instruction Learning Package (SILP) was used for treatment between the pre-test and post-test. The research hypotheses formulated were tested at 0.05level of significance. Data collected were analyzed with descriptive and inferential statistics. The findings recorded significant effect of mentoring on secondary school science students’ attitude towards environmental practices. Based on the findings of the study, it was thus recommended among others that, science teachers should employ mentoring strategy in teaching topics on ‘Environment’ to encourage better environmental practices among their students.